PUMA – pooled uranium miners analysis: cohort profile. (31st January 2020) - Rage, Estelle; Richardson, David B; Demers, Paul A; Do, Minh; Fenske, Nora; Kreuzer, Michaela; Samet, Jonathan; Wiggins, Charles; Schubauer-Berigan, Mary K; Kelly-Reif, Kaitlin; Tomasek, Ladislav; Zablotska, Lydia B; et al.
Abstract : Objectives: Epidemiological studies of underground miners have provided clear evidence that inhalation of radon decay products causes lung cancer. Moreover, these studies have served as a quantitative basis for estimation of radon-associated excess lung cancer risk. However, questions remain regarding the effects of exposure to the low levels of radon decay products typically encountered in contemporary occupational and environmental settings on the risk of lung cancer and other diseases, and on the modifiers of these associations. These issues are of central importance for estimation of risks associated with residential and occupational radon exposures. Methods: The Pooled Uranium Miner Analysis (PUMA) assembles information on cohorts of uranium miners in North America and Europe. Data available include individual annual estimates of exposure to radon decay products, demographic and employment history information on each worker and information on vital status, date of death and cause of death. Some, but not all, cohorts also have individual information on cigarette smoking, external gamma radiation exposure and non-radiological occupational exposures. Results: The PUMA study represents the largest study of uranium miners conducted to date, encompassing 124 507 miners, 4.51 million person-years at risk and 54 462 deaths, including 7825 deaths due to lung cancer. Planned research topics include analyses of associations between radon exposure and mortality due to lung cancer, cancers other than lung, non-malignant disease, modifiers of these associations and characterisation of overall relative mortality excesses and lifetime risks. Conclusion: PUMA provides opportunities to evaluate new research questions and to conduct analyses to assess potential health risks associated with uranium mining that have greater statistical power than can be achieved with any single cohort.